Case report: A case report of Alport syndrome caused by a novel mutation of COL4A5 - Pan, Shujun; Yu, Rizhen; Liang, Shikai (Frontiers in Genetics, 2023)
Alport syndrome (#308940) is an X-linked genetic disease with clinical manifestations, such as hematuria, proteinuria, renal insufficiency, and end-stage renal disease. The disease is characterized by thinning of the glomerular basement membrane in the early stages and thickening of the glomerular basement membrane in the late stages, and may be associated with ocular lesions and varying degrees of sensorineural deafness.Herein, we report a case of Alport syndrome caused by a de novo mutation in COL4A5. The patient was a young male with clinical manifestations of hematuria and massive proteinuria who was diagnosed with Alport syndrome based on renal pathology and genetic testing.